The immunomodulatory effect of propolis on receptors expression, cytokine production and fungicidal activity of human monocytes - Bufalo, Michelle Cristiane [UNESP]; Bordon-Graciani, Ana Paula [UNESP]; Conti, Bruno Jose [UNESP]; Golim, Marjorie de Assis [UNESP]; Sforcin, Jose Mauricio [UNESP] (Wiley-Blackwell, 2014)
ObjectivesPropolis is a beehive product and its immunomodulatory action has been documented; however, little is known concerning its mechanisms of action on human cells. Propolis influence on the initial events of the immune response was assessed, evaluating cell markers, cytokine production and the fungicidal activity of human monocytes.MethodsToll-like receptor (TLR)-2, TLR-4, human leukocyte antigen-DR and cluster of differentiation (CD)80 expression by human monocytes was assessed using a FACSCalibur flow cytometer, cytokine production (tumour necrosis factor (TNF)- and interleukin (IL)-10) was determined by ELISA and the candidacidal activity was investigated after monocytes incubation with propolis and challenged with Candida albicans. The role of TLR-2 and TLR-4 on propolis action was assessed as well.Key findingsPropolis upregulated TLR-4 and CD80 expression and affected TNF- and IL-10 production, depending on concentration. Propolis also increased the fungicidal activity of monocytes. Cytokine production was decreased by blocking TLR-4, whereas the fungicidal activity was affected by blocking TLR-2.ConclusionsPropolis exerted an immunomodulatory action on cell receptors, cytokine production and fungicidal activity of human monocytes without affecting cell viability and depending on concentration. TLR-2 and TLR-4 may be involved in its mechanism of action.
Keywords: cytokines; monocytes; propolis; Toll-like receptors